Separation Of Radioisotope 113mIn Using Column Chromatography Based on Silica Gel Matrix - Duyeh Setiawan; M Basit Febrian; Yanuar Setiadi (Molekul, 2018)
Radioisotope indium-113m (113mIn) with half-life, T1/2 = 1.7 hours and gamma energy, Eg = 391 keV is suitable and meets the criteria as radiotracer in industry. 113mIn radioisotope was obtained from tin-113 decay (113Sn, T1 / 2 = 115 days) of 112Sn (n,g) 113Sn neutron activation in nuclear reactor. The process of separation of radioisotope 113mIn using column chromatography method based on silica gel matrix using 0.05 M HCI solution. Radionuclide and radiochemical purity tests were performed using the gamma-spectrometry method and paper chromatography. The final product specification in the form of 113mInCl3 is clear solution, pH 2, obtained yield of 81.83%, radionuclide purity of 90.22%, radiochemical purity of 91.61 ± 0,29% and stable for 3 days at room temperature.